민간투자사업 성과평가 모델 개발 및 적용 - 도로 부문 사업을 중심으로 - 박현; 박인석; 이신; Park, Hyeon; Park, Inseok; Lee, Shin (한국건설관리학회 논문집, 19(2), 2018)
The aim of this paper is to develop a performance evaluation model for PPP (Public-Private Partnership) projects that appropriately reflects the important traits that are unique to PPP projects. To this end, 1) it defines a set of distinct perspectives involved in the PPP projects and their associated success factors that might differ amongst the perspectives; 2) it identifies the key performance indicators and suggests the performance evaluation criteria for each indicator; and 3) it builds a performance evaluation model by matching the success factors from each perspective with performance measure criteria as well as applies the model to the two selected BTO road projects in Korea. The process of model construction and its application confirms significant differences between the main stakeholder perspectives typically involved in PPP projects, which highlights the need for an evaluation model tailored for PPP projects by taking into account the distinct perspectives. The results from the PPP evaluation model developed in the study is compared against the results from the existing ex-post evaluation model for construction projects in general. The former shows a closer match with the results from the user satisfaction survey conducted. This new evaluation framework and the performance indicators entailed in it permits a balanced evaluation of PPP projects as it takes into account different perspectives involved in PPP projects as well as an understanding of the factors affecting the success of PPP projects. While the construction of the model is based on transport projects, it is applicable to different types of PPP projects through variation with the weight allocation amongst different success factors and/or additions or other adjustments to the performance evaluation criteria as required. 본 논문은 민간투자사업의 특수성을 반영한 성과평가 모델 개발을 목적으로 한다. 성과평가 모델 개발을 위해 첫째, 문헌연구를 통하여 민간투자사업 주요 관점과 관점별 성공항목을 정의하고, AHP 설문조사를 통하여 가중치를 산정하였다. 둘째, 민간투자사업 성과에 영향을 미치는 핵심 성과요인을 도출하고, 이를 평가할 수 있는 평가항목을 제안하였다. 셋째, 관점별 성공항목과 평가항목을 매칭함으로써 민간투자사업 성과평가 모델을 구축하였다. 성과평가 모델 개발과 적용을 통해 민간투자사업 이해관계자 사이의 첨예한 관점의 차이가 존재함을 파악할 수 있었다. 이는 다양한 이해관계자의 관점을 균형있게 반영한 민간투자사업의 종합적인 평가의 필요성을 보여준다. 본 연구에서 제시한 성과평가 모델의 평가 결과와 기존의 건설공사 사후평가 결과를 비교해보면, 본 연구의 평가 점수가 이용자 만족도 조사 결과와 유사하다. 건설공사 사후평가에 비해 본 연구의 평가모델은 다양한 이해관계자의 만족도 및 관점을 반영하였기 때문으로 판단된다. 본 연구에서 개발한 성과지표의 결과를 통해 다양한 관점을 고려한 민간투자사업의 성과를 측정할 수 있으며, 어떠한 성공요인 및 평가항목이 프로젝트 성공에 영향을 미치는지 파악할 수 있다. 또한, 본 모델의 프로세스를 기반으로 주요관점 및 성공항목의 가중치 변화와 평가항목의 가감을 통해 도로 시설물을 제외한 민간투자사업 프로젝트에도 적용이 가능할 것으로 기대된다.